Adapt or Perish: A New Approach for Industry Needs-Driven Master’s Level Low-Carbon Energy Engineering Education in the UK - Paul Rowley; Caroline Walker (Energies, 2020)
This paper describes the results of recent research carried out with the UK energy sector to assess low-carbon related skills gaps and training requirements at the masters-level. Via iterative engagement across the industry, the characteristics of the market for new ‘needs-driven’ industry-focussed masters-level training offerings were defined. The results, taken together with the outcomes of a gap analysis of existing masters-level training, support the creation of a new framework for masters-level energy education that will more effectively meet the growing unmet need for such skills in the UK and beyond. The outcomes of the research indicate that flexibility in both delivery mode and curriculum content across both technical and non-technical disciplines is essential, along with improved supplier agility to rapidly develop new courses in evolving engineering specialisations. Without responding effectively to such demands from industry, we conclude that the advanced skills needed across the highly dynamic UK and global energy engineering sector will be in increasingly short supply.